Effect of temperature on the microstructure of hot pressed Co based Co-Cr-Mo alloy - Somunkiran, I.; Balin, A. (Natl Inst Optoelectronics, 2013)
In this study, biocompatible Co-based Co-Cr-Mo alloy powder produced by direct-resistant hot-pressing technique at different temperatures. The effect of pressing temperature on microstructure and mechanical properties of the samples produced were determined. The powder consisting Of 67.5% Co (99.5% purity-325mesh), 27.5% Cr (99% purity-325mesh) and 5% Mo (purity 99.95%-325mesh) was homogeneously mixed by the adding polyethylene glycol lubricant. The powder mixtures prepared were directly hot pressed under 115 bar at 750, 800, 850, 900 C for 5 minutes. Density, microstructure and some mechanical characteristics of the samples produced were investigated. The density of the sintered specimens increased with the temperature, except the specimen at 850 C in which porosity increased, due to the local microstructural segregation.
Keywords: Hot Pressing; Orthopedic Implants; Co-Cr-Mo Alloy; Powder Metallurgy